Categorical modeling to evaluate road safety at the planning level - Sara Ferreira (2011)
The most efficient strategy to ensure long term road network safety is to integrate road safetyanalysis into the planning process of a network or a corridor. Safety planning decision-supporttool outcomes should be reliable and realistic, taking into account the main characteristics of thisparticular level, which is characterized by scant and generalized data. However, the toolsdeveloped and presented in previous studies are based on models with a quantitative response,usually the number of accidents, which may not be appropriate for this level. In order to developa more suitable tool while maintaining a measure assessment character, this work presents aqualitative response model whose outcome is the risk of occurring three degrees of hazards: low,medium and high. In the present study, an ordered probit model was applied to an urban roadnetwork using Porto (Portugal) data covering a 5-year period. Hazard categories were definedusing accident frequency to reflect a measure of the safety of the road network studied.The developed model provides a safety risk analysis of a road network or a corridor for a futureperiod, considering road data that are easy to gather or estimate at the planning level, such as landuse, traffic volume, etc.This methodology was applied to various segment scenarios to provide an evaluation of changingroad features. Furthermore, a comparison between qualitative and quantitative model outcomes ispresented, showing the former as an appropriate model that enables a risk analysis approach.